CHARACTERISTICS OF DUAL EDUCATION IN THE TRAINING OF ENGINEERING BACHELORS IN HIGHER EDUCATION INSTITUTIONS - Kodirov Ismail Norkobilovich (Western European Studies, 2024)
The article examines the features of dual education, which allows to solve the problem of professional training of personnel, taking into account the interests of higher education institutions and employer enterprises in the training of engineers in the field of alternative energy in higher education countries. The dual education system is an effective and flexible mechanism that enables the training of highly qualified specialists required in the activities of enterprises of various sectors in the modern conditions of the market economy
Keywords: production and higher education institutions; dual education; enterprises of various sectors